President's Message - Mushayandebvu, Barbara (Operating Room Nurses Association of Canada Journal, 2017)
I do hope everyone celebrated each other and our achievements for Perioperative Nurses Week in November. The theme, Perioperative Nurses – The Voice of Our Patients, speaks to what we do, on a daily basis, and often take for granted. It is through our role as patient advocates that we become the voice of our patients. This advocacy role is exemplified when we uphold and practice according to the ORNAC Standards, Guidelines and Position Statements for Perioperative Registered Nurses. ORNAC’s Mission, Vision and Core Values support patient advocacy through the promotion and advancement of excellence in the provision of safe perioperative care for patients and guiding perioperative nurses on a path to be leaders in this area.